Administrative Optimization Strategy to Achieve Good Governance at SD Muhammadiyah 01 Pematangsiantar - Nasution, Bachtiar Abror; Elfrianto, Elfrianto (Indonesian Journal Education, 2023)
This study explores the strategy of optimizing governance at SD Muhammadiyah 01 Pematangsiantar through a qualitative approach. Problem identification involves participatory observation and document analysis. Optimization strategies involve the use of information technology, updating administrative procedures, and increasing staff capacity through training. The implementation of the strategy shows a positive impact, improving the operational efficiency and management of the school. Improvements in the quality of education, parental involvement, and a positive work climate are also visible. This research contributes to the concepts of educational governance and human resource management. In conclusion, optimizing administration not only increases efficiency, but also opens up opportunities to improve the quality of education at SD Muhammadiyah 01 Pematangsiantar